2021
DOI: 10.1177/00048674211046891
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and 5-year trend of incidence for medical illnesses after the diagnosis of bipolar disorder: A nationwide cohort study

Abstract: Objective: Medical comorbidities are prevalent in patients with bipolar disorder. Evaluating longitudinal trends of the incidence of medical illnesses enables implementation of early prevention strategies to reduce the high mortality rate in this at-risk population. However, the incidence risks of medical illnesses in the early stages of bipolar disorder remain unclear. This study investigated the incidence and 5-year trend of medical illnesses following bipolar disorder diagnosis. Methods: We identified 11,88… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…26,34,35 In addition, laboratory studies have indicated that lithium administered at therapeutic levels ameliorates pathological hypertrophy and cardiac fibrogenesis in cellular and rat models of myocardial infarction. 6,36 Lithium likely achieves cardioprotective effects by inhibiting inflammatory responses, reactive oxidative stress, and endothelial dysfunction 37,38 and involves numerous signaling pathways. 39 Similarly, mechanistic studies have discovered that valproic acid protects cardiomyocytes and neurons from ischemic injury by modulating histone deacetylase activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…26,34,35 In addition, laboratory studies have indicated that lithium administered at therapeutic levels ameliorates pathological hypertrophy and cardiac fibrogenesis in cellular and rat models of myocardial infarction. 6,36 Lithium likely achieves cardioprotective effects by inhibiting inflammatory responses, reactive oxidative stress, and endothelial dysfunction 37,38 and involves numerous signaling pathways. 39 Similarly, mechanistic studies have discovered that valproic acid protects cardiomyocytes and neurons from ischemic injury by modulating histone deacetylase activity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, clinical studies have revealed that lithium treatment reduces the risk of cardiovascular disease in patients with bipolar disorder 26,34,35 . In addition, laboratory studies have indicated that lithium administered at therapeutic levels ameliorates pathological hypertrophy and cardiac fibrogenesis in cellular and rat models of myocardial infarction 6,36 . Lithium likely achieves cardioprotective effects by inhibiting inflammatory responses, reactive oxidative stress, and endothelial dysfunction 37,38 and involves numerous signaling pathways 39 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations